Synthesizing Evidence from Diagnostic Accuracy TEsts: The SEDATE guideline - Sotiriadis, Alexandros; Papatheodorou, Stefania; Martins, Wellington (My University, 2016)
Published by John Wiley & Sons Ltd.Although commonly overlooked during the writing and reporting process, most readers will look at only the abstract, so it is essential to convey as much quantitative information as possible, given the space limitations set by the journal. Suggested subheadings include 'Introduction' (specifying the current state of knowledge in the field, the gap that this study aims to cover, i.e. objectives), 'Methods' (search strategy, eligibility criteria, outcomes and statistical analysis), 'Results' (study selection and main results with numerical estimates) and 'Conclusion' (clinical interpretation of results and suggestions for future research).